Musically induced ASMR : an amalgamated experience - Kobayashi, Juri (2015)
Musically induced ASMR is an Autonomous Sensory Meridian Response triggered by music. The term ASMR is best known on the internet by communities who report experiencing this phenomenon. It is most simply understood as an experience like musical chills, however can be triggered by nearly any form of stimuli. The current study employed grounded theory, a meticulous and established qualitative research method for developing theory that serves to explain salient characteristics of a particular phenomenon; to theorize the nature and significance of musically induced ASMR and ASMR in general. Based on the data collected, the study confirmed the existence of musically induced ASMR and demonstrates this concept’s analogous psychological, physiological, and emotional characteristics with musical chills through comparison with prior research. The study established the term musically induced ASMR to describe a phenomenon, for which previous studies have struggled to assign competent descriptive terminology such as, chills, thrills or frisson. As a core characteristic of the phenomenon, it was found that ASMR stimulates a sense of selfawareness, which initiates other psychological, physical and emotional responses.